An Appraisal and Popular Notion Surrounding The Arab Spring: The Marxist Analyses - Obah-Akpowoghaha, Nelson Goldpin; Tarro, Momodou Lamin; Adekunle, Ogunmilade (Advances in Social Sciences Research Journal, 2020)
Studies on the Arab Spring have advanced economic reason as propeller to various ugly events that have changed the face of most states in the Middle East and North Africa. Most of this literature undermined the influenced of external motivations and knowledge which have been instrumental to certain occurrences in developing countries. This piece identified existing stereotypes which have been underscored by western thoughts and advanced an opposing narrative. This narrative seems to gain less attention compare to western views on the issues that surround the Arab quake. However, this investigation relied on secondary sources of data which is mainly extant literature vis-à-vis Marxist theories with the view of de-emphasising certain notions and bring to the fore realities of events in the Middle East and North Africa.